The English Language and the Secretarial Activity in the Corporate Environment: A Review of Roles - Lourenço, José Roberto (The ESPecialist, 2014)
This paper aims to present the results of a piece of research on professional activities carried out with secretaries who work in big companies in the city of São Paulo and who have the English language as an important working tool. Researchers of the needs analysis area played an important role in the procedures followed for this study and the discussion of the findings. The approach aims essentially at knowing the most important and frequent activities in the daily routine of the bilingual secretary, as well as the necessary skills and means of communication to do them. The final results will make it possible to teach the subject English language more appropriately in the Secretarial Course at Faculdade de Tecnologia de São Paulo, making it compatible with the demands of the job market today.